7x^2+4x-15=49-44x

Simple and best practice solution for 7x^2+4x-15=49-44x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x^2+4x-15=49-44x equation:


Simplifying
7x2 + 4x + -15 = 49 + -44x

Reorder the terms:
-15 + 4x + 7x2 = 49 + -44x

Solving
-15 + 4x + 7x2 = 49 + -44x

Solving for variable 'x'.

Reorder the terms:
-15 + -49 + 4x + 44x + 7x2 = 49 + -44x + -49 + 44x

Combine like terms: -15 + -49 = -64
-64 + 4x + 44x + 7x2 = 49 + -44x + -49 + 44x

Combine like terms: 4x + 44x = 48x
-64 + 48x + 7x2 = 49 + -44x + -49 + 44x

Reorder the terms:
-64 + 48x + 7x2 = 49 + -49 + -44x + 44x

Combine like terms: 49 + -49 = 0
-64 + 48x + 7x2 = 0 + -44x + 44x
-64 + 48x + 7x2 = -44x + 44x

Combine like terms: -44x + 44x = 0
-64 + 48x + 7x2 = 0

Factor a trinomial.
(-8 + -1x)(8 + -7x) = 0

Subproblem 1

Set the factor '(-8 + -1x)' equal to zero and attempt to solve: Simplifying -8 + -1x = 0 Solving -8 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -1x = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -1x = 0 + 8 -1x = 0 + 8 Combine like terms: 0 + 8 = 8 -1x = 8 Divide each side by '-1'. x = -8 Simplifying x = -8

Subproblem 2

Set the factor '(8 + -7x)' equal to zero and attempt to solve: Simplifying 8 + -7x = 0 Solving 8 + -7x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -7x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -7x = 0 + -8 -7x = 0 + -8 Combine like terms: 0 + -8 = -8 -7x = -8 Divide each side by '-7'. x = 1.142857143 Simplifying x = 1.142857143

Solution

x = {-8, 1.142857143}

You can always share this solution

See similar equations:

| 3x^3+9x^2+6x=0 | | x^2-3x-18=0 | | x^2-63x+60=0 | | 2x(4x-7)+3=(2x-7)(3x+4)+2x^2 | | 8x^3+10xy+6x^2y^5=0 | | 2X(X^2-4X+7)= | | 2x^2-5x-5=0 | | 2x^2-38x=7x^2-3x-24 | | 9p^2+18p=10 | | x^2-5x=6 | | 2x^2-4=-204 | | 2x^2-8=-170 | | x(5x+10)=2x^2-3x+30 | | 8x^2-8x-1=0 | | 2x^2-9x-2=0 | | 2x^2=10x+3 | | y^2-4y+8=0 | | 42t^2-13tv-42v^2= | | 6s^2-13s+6= | | 2w^2+9w+9= | | 4x^7-20x^5+16x^8= | | x^2-16=0 | | x^2=81 | | 3x^2+6x=0 | | x^2-7x=0 | | y^2+6y+8=0 | | 5x^4+31x^2+6=0 | | x^2-10-4x-11=0 | | 5x^3+(2x-12)=1 | | m^2-6m+8=0 | | m^2+10m+9=0 | | m^2+5m+6=0 |

Equations solver categories